Exploring the Relationships of Crime Victimization with Depression, Anxiety, and Loneliness in Twin Families - Gonggrijp, B.M.A. (Journal of developmental and life-course criminology, 2023)
Crime victimization is associated with a more unfavorable health profile. We examined associations of victimization of property, violence, and sexual crime with mental health indices for depression, anxiety, and loneliness and explore their etiology in Dutch twin families. The data were collected from adult twins, their parents, siblings, spouses, and offspring participating in longitudinal survey studies of the Netherlands Twin Register (N = 19,867). First, we tested if there is an association between victimization and loneliness, anxiety, and depression at the population level. Second, discordant twin pairs were identified, where one twin was a crime victim and the cotwin was not. This design allows controlling for confounding by shared environment and genetic factors. Third, a longitudinal comparison was made of pre- and post-victimization data in victims, their family members, and unrelated individuals. At the population level, victimization was associated with increased depression, anxiety, and loneliness, except for property crime, which was not associated with depression and anxiety. The associations were strongest for violent and sexual crimes. Within discordant twin pairs, no significant differences were found between the victimized and non-victimized twins. These results confirm that crime victimization is associated with adverse mental health outcomes and loneliness, with the strength of this association differing per type of crime. There is no strong evidence that the relationship between victimization and mental health or loneliness follows a simple causal model, as the relationship can be partly explained by genetic and shared environmental confounding. These results also suggest that victims of sexual and violent crimes may already experience more mental health problems before victimization than non-victims, and that individuals with more mental health problems and loneliness are at increased risk of becoming a victim.